Representations of Colors and Their Connotations on the Covers of Kafka’s Novels and Saad Said’s Novels: A Comparative Study - Dr. Wasan Morshid Mahmoud (Journal of College of Education, 2025)
This study undertakes a comparative analysis of narrative works that have engaged with a subject of both scholarly interest and creative inquiry—namely, the representations of colors and their connotations on the covers of Kafka’s novels and Saad Said’s novels. The covers reveal that they draw their aesthetic from an array of uninhibited color pigments, each embracing a distinctive thematic quality expressed through unique visual mechanisms. Moreover, the research seeks to uncover the extent to which ideas converge, ensuring that such convergence is vividly manifested in creative outputs through the comparison of innovative modern literary expressions. Accordingly, the study examines a literary culture spanning two different eras—diverging in language and cultural context, yet converging in methodology and thematic focus—to explore the connotations of these colors and their representations. This endeavor epitomizes the mission of comparative studies, which at its core is dedicated to drawing insightful parallels between the literatures of different nations, exploring the dynamics of influence and reciprocal impact.